Drivers of negative caesarean section experiences in Haut Uélé Province, Democratic Republic of the Congo - Valentin Bwembola Boya; Jules Moti Kangite; Monizi Mawunu; Jean-Pau; Augustin Makangu Tshitadi; Marie-Claire Ohambe Omanyondo; Roger Mwimba Mbungu (Orapuh, Inc., 2024)
Introduction Caesarean section is a commonly performed obstetric procedure that is often associated with a higher rate of peri- and post-operative complications. These complications include anaesthetic problems, haemorrhage, lower uterine segment tears, bladder and bowel injuries, ureteral lesions, infections, thromboembolic risks, anaemia, and bowel transit disorders. These issues can negatively impact women's perceptions and experiences of caesarean section, affecting their overall experience of the procedure. Purpose This study aims to identify the factors associated with negative experiences of caesarean section to help improve women's experiences with this procedure in Haut Uélé Province. Methods This was a quantitative, descriptive, and correlational study designed to explore the determinants of negative experiences among women who had undergone caesarean sections in this local context. Results The study's findings demonstrated the positive impact of midwife training on reducing negative experiences of caesarean sections. Factors associated with negative perceptions included a lack of communication about the diagnosis before surgery, inadequate disclosure of the need for a caesarean section, an unhealthy hospital environment, and poor family perceptions of the procedure. Conclusion Improving communication, enhancing the hospital environment, and fostering better family understanding of caesarean sections can help reduce the negative experiences associated with this procedure. Enhanced training for midwives plays a critical role in achieving more positive outcomes for women undergoing caesarean sections.